Bridging to possible: Empowering visually impaired students through assistive technology rehabilitative training to become better students and future employees - Radwa, Elshemy; Fahad, Alzahrani; Shereen, Fawzy; Fahad, Almasoudi; Yasser, Moussa; Mohamed, Elsayed (Edelweiss Applied Science and Technology, 2025)
Assistive technology (AT) has evolved rapidly and continues to develop among visually impaired students (VIS). The inclusion of VIS in mainstream education and employment is essential for building an inclusive society. However, it has been reported that VIS face numerous challenges in accessing and utilizing education and employment opportunities. This research paper aims to explore the effectiveness of assistive technology-based training in empowering VIS to become better future employees. The paper reviews various assistive technologies and their applications in facilitating learning and employment opportunities for visually impaired students. The study then uses a tri-level, mixed-method design to examine the impact of rehabilitative training that is based on assistive technology on the academic performance and employability of visually impaired students. The findings of the study reveal that assistive technology-based training has a significant positive impact on the academic performance and employability of VIS. The study recommends the integration of assistive technology-based training into the mainstream education system to provide equal learning and employment opportunities for visually impaired students.